تطور العدالة الدستورية في الجزائر - لزهر بوغازي; رانية حمزاوي (My University, 2025)
Summary This memo addresses the development of constitutional justice in Algeria, considering it as one of the fundamental pillars for upholding the principle of constitutional supremacy and ensuring its respect by various authorities. The Algerian constitutional system has gone through several reform stages, reflecting the legislator's efforts to enhance the oversight of the constitutionality of laws, both in terms of the body authorized to carry out this oversight and the mechanisms and powers involved. The study focuses on tracing the historical and institutional framework of constitutional justice, starting with the establishment of the Constitutional Council in 1989, up to the creation of the Constitutional Court under the 2020 constitutional amendment, which marked a significant shift in the organization of constitutional justice. The study also aimed to highlight the strengths and shortcomings of the current constitutional system by analyzing the legal texts regulating the Constitutional Court, along with a comparative analysis of its experience with other models. The findings of the study indicate that the success of constitutional justice in fulfilling its role is closely linked to the activation of its mechanisms, the provision of guarantees for the independence of its members, and the raising of public awareness regarding the importance of raising constitutionality challenges as a tool for protecting rights and freedoms. ............................ ملخص تناولت هذه المذكرة تطور العدالة الدستورية في الجزائر، باعتبارها أحد الأسس الرئيسة لتأكيد مبدأ سمو الدستور وضمان احترامه من قبل مختلف السلطات. فقد شهد النظام الدستوري الجزائري عدة مراحل إصلاحية تعكس جهود المشرع في تعزيز الرقابة على دستورية القوانين، سواء من حيث تحديد الجهة المخولة بتنفيذ هذه الرقابة أو من حيث آلياتها وصلاحياتها. تركز الدراسة على تتبع الإطار التاريخي والمؤسساتي للعدالة الدستورية، بدءًا من تأسيس المجلس الدستوري عام 1989، وصولًا إلى إنشاء المحكمة الدستورية بموجب التعديل الدستوري لعام 2020، وهو ما مثل نقلة نوعية في تنظيم العدالة الدستورية في البلاد. كما سعت الدراسة إلى تسليط الضوء على جوانب القوة والقصور في النظام الدستوري الحالي، من خلال تحليل النصوص القانونية المنظمة للمحكمة الدستورية، مع إجراء مقارنة لتجربتها مع بعض النماذج المقارنة. وقد خلصت الدراسة إلى أن نجاح العدالة الدستورية في أداء مهامها يرتبط بشكل وثيق بتفعيل آلياتها القانونية، وتوفير الضمانات اللازمة لاستقلالية أعضائها، بالإضافة إلى تعزيز وعي الأفراد بأهمية الدفع بعدم الدستورية كأداة أساسية لحماية الحقوق والحريات. ........................... Conclusion Cette note aborde l'évolution de la justice constitutionnelle en Algérie, la considérant comme l'un des piliers fondamentaux du respect du principe de suprématie constitutionnelle par les différentes autorités. Le système constitutionnel algérien a connu plusieurs réformes, reflétant les efforts du législateur pour renforcer le contrôle de la constitutionnalité des lois, tant en ce qui concerne l'organe habilité à exercer ce contrôle que les mécanismes et pouvoirs impliqués. L'étude s'attache à retracer le cadre historique et institutionnel de la justice constitutionnelle, de la création du Conseil constitutionnel en 1989 à la création de la Cour constitutionnelle suite à la révision constitutionnelle de 2020, qui a marqué une évolution significative dans l'organisation de la justice constitutionnelle. L'étude vise également à mettre en évidence les forces et les faiblesses du système constitutionnel actuel en analysant les textes juridiques régissant la Cour constitutionnelle, ainsi qu'en procédant à une analyse comparative de son expérience avec d'autres modèles. Les résultats de l'étude indiquent que le succès de la justice constitutionnelle dans l'accomplissement de son rôle est étroitement lié à l'activation de ses mécanismes, à la garantie de l'indépendance de ses membres et à la sensibilisation du public à l'importance du recours en inconstitutionnalité comme outil de protection des droits et libertés.
Keywords: Keywords: Constitutional Court; Constitutional Council; Constitutional Justice; plea of unconstitutionality; Constitutional Jurisdiction.; الكلمات المفتاحية : المحكمة الدستورية، المجلس الدستوري ، العدالة الدستورية، الدفع بعدم الدستورية، القضاء الدستوري.; Mots-clés : Cour constitutionnelle; Conseil constitutionnel; justice constitutionnelle; exception d'inconstitutionnalité; juridiction constitutionnelle.